Building-related asthma in Denver office workers. - Hoffman, R E (1993)
OBJECTIVES. Reported cases of building-related asthma and hypersensitivity pneumonitis among workers in a Denver office building prompted an epidemiologic investigation. METHODS. A cross-sectional, self-administered survey of employees in the office building of the reported cases was compared with that of employees in a comparison building. RESULTS. A significant excess of respiratory disease existed among 512 Denver workers (case building) compared with 281 office workers in a suburban agency (control building). Denver employees had a higher prevalence of respiratory symptoms, and the prevalence of physician-diagnosed asthma with onset or exacerbation since building occupancy was 4.9 times greater for Denver employees than for suburban employees. Asthma was not associated with any particular ventilation system in the building. Water incursion from a below-grade wall may have contributed to the problem, but the etiology is unknown. CONCLUSIONS. This investigation provided evidence of office building-related asthma. Individual cases may be sentinel events for other cases of work-related asthma or hypersensitivity pneumonitis and may indicate a need for public health investigation of remediable causes.